Application of Interactive Games on Tourism Objects Based on Augmented Reality Gamification - Aristana, Made Dona Wahyu; Sanusi, Rikcy; Sudipa, I Gede Iwan; Aditama, Putu Wirayudi; Wiguna, I Komang Arya Ganda (Information Technology and Science (ITScience), 2024)
The development of information technology is always growing rapidly, especially in the field of android smartphones. Android smartphones can now be obtained at a fairly affordable price. With rapid development, there are so many innovations that can be developed by the smartphone itself, even the tourism sector such as The Sila's Agroutourism can get the impact of several innovations that exist along with the times such as Augmented Reality. In this research, the author uses two augmented reality methods, namely Marker Based Tracker and also Markerless. Where Marker based tracker is a method that uses image illustrations in the form of QR codes or special logos to identify an object in the Augmented Reality application. While Markerless is a method that does not require a marker or image to display the object. So that this research produces an augmanted reality game using the marker-based tracker method and also markerless which takes the GPS tracker method as its markerless method. This test uses 3 tests, namely Blackbox testing, Response Time testing and also User Experience Questioner (UEQ). Where the UEQ results filled in by 35 respondents get results above average (Excelent). So that it shows that this game is good and as expected.